Escola de Tururukari Uka : uma análise do papel da escola na formação da identidade linguísticocultural dos Kambeba - Oliveira, Marileny de Andrade de (2018)
This study analyzes the role of the indigenous school in the production of the linguistic-cultural identity of the Kambeba of Tururukari-Uka. The indigenous Kambeba ethnic group, soon after the first centuries of colonization, were considered extinct. However, in the 1980, the patriarch, Mr. Valdomiro Cruz, brings up the voice of this population that seeks its ethnic reassertion. The village Kambeba Tururukari-Uka, located in the rural area of the municipality of Manacapuru - AM, is the main stage of this history of resistance and ethnic struggle: the situation of conflict due to the appropriation of the land where they live; the clashes of interethnic contacts, since they live in the vicinity of two non-indigenous communities; and the process of strengthening the language. The theoretical contribution was based on references such as Luciano (2006), Melatti (1994), Mircea Eliade (1994), Couto (2012), Hanks (2008), Rajagopalan (2003), Bauman ) among other authors. The data that compose the corpus of this research were collected through participant observation, application of semistructured questionnaires, interviews and the registration of words from the Swadesh list. Through the analysis of the results, it is concluded that the Tururukari-Uka natives maintain a relationship of transculturality as a form of resistance and struggle for their rights within the surrounding society, understood as a collectivity constituted both by indigenous peoples of other ethnic groups and also by non Indians. Gradually, they regain the pride of being Indian, in a conception that contrasts with the mythical and stereotyped vision of the "Indian being" disseminated by the Europeans. In this cultural hybridity, the community school plays a role as the protagonist, through indigenous school education, of the process of disseminating the Kambeba language and culture to the new generation, acting in the identity formation of the Kambeba, in the process of strengthening the practices of ethnic movements, in the movements that claim for the rights to land, health, the preservation of their culture, and differentiated education. In this way, the silence of almost two centuries drives the suppressed cry that is made especially in the Amazonian society in favor of the recognition of an ethnicity given by extinct in the last century. Keywords: Kambeba; Indigenous School Education; Language. Culture